Determinants of patient activation and its association with cardiovascular disease risk in chronic kidney disease: A cross‐sectional study - Thomas J. Wilkinson; Katherine Memory; Courtney J. Lightfoot; Jared Palmer; Alice C. Smith (Wiley, 2021)
Abstract Background Patient activation describes the knowledge, skills and confidence in managing one's own health. Promoting patient activation is being prioritized to reduce costs and adverse outcomes such as cardiovascular disease (CVD). The increasing prevalence of chronic kidney disease (CKD) presents a need to understand the characteristics that influence patient activation and the effect on health outcomes. Design Cross‐sectional study. Setting and participants Patients with non‐dialysis CKD recruited from 14 sites (general nephrology and primary care) in England, UK. Outcome measures Patient activation was measured using the PAM‐13. Demographic and health‐related variables, self‐reported symptom burden, health‐related quality of life (HRQOL), socioeconomic status (SES), were assessed as determinants of patient activation. Major CVD risk factors included hypertension, dyslipidaemia, obesity and hyperkalaemia. Results 743 patients were included (eGFR: 32.3 (SD17.1) mL/min/1.73 m2, age 67.8 (SD13.9) years, 68% male). The mean PAM score was 55.1 (SD14.4)/100. Most patients (60%) had low activation. Those with low activation were older (P<.001), had lower eGFR (P = .004), greater number of comorbidities (P = .026) and lower haemoglobin (P = .025). Patients with low activation had a 17% greater number of CVD risk factors (P < .001). Risk factors in those with low activation were being older (P < .001) and having diabetes (P < .001). Conclusion This study showed that only a minority of CKD patients are activated for self‐management. Our findings help better understand the level of activation in these patients, particularly older individuals with multimorbidity, and further the knowledge regarding the characteristics that influence activation. Patient or Public Contribution Patients were involved in the design of main study.